A very uncommon clinical entity: Lansoprazole-induced symptomatic hyponatremia in a young woman - Kaplan, Mustafa; Tanoğlu, Alpaslan; Düzenli, Tolga; Çakır Güney, Başak; Önal Taştan, Yeşim (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Kaplan M, Tanoğlu A, Düzenli T, Çakır Güney B, Önal Taştan Y. A very uncommon clinical entity: Lansoprazole-induced symptomatic hyponatremia in a young woman. Turk J Gastroenterol 2020; 31(12): 957-9.